Back to the Future: Library Book Clubs for Individuals with Intellectual Disability (ID) - Matthew Conner; Leah Plocharczyk (The International Journal of Information, Diversity, & Inclusion, 2019)
This article provides context for library services for individuals with intellectual disability (ID) and then provides a case study and preliminary data on new efforts in the field for public libraries, school media centers, and academic libraries connected with the educational system. While many libraries are dedicated to serving diverse populations, they have done little to support individuals with ID who have difficulty using library services and accessing their collections. Efforts to advertise, to develop specialized collections, and to utilize assistive technology have floundered on high costs and low returns. These shortcomings are especially critical for adults with ID. While the law mandates the inclusion of individuals with ID in the public school system, there are few opportunities for education, employment, or socializing for those who age out; the library, as a fundamental public institution, is one of the few resources available to them. For the benefit of both libraries and adults with ID, it is critical that libraries develop improved services for this group of patrons. The case study in this article provides data on a book club for persons with ID held at an academic library and based on the model of the Next Chapter Book Club (NCBC) organization. By comparing data between the case study and 30 similar book clubs at public libraries throughout the nation, the article develops a profile of what these book clubs do and how to measure their successes. We conclude that such clubs represent a low-cost, effective way for libraries to support persons with ID that helps libraries fulfill their mission of serving diverse groups and provides critical support to this particular population.